Good enough parenting : a six-point plan for a stronger relationship with your child - Cavell, Timothy A.; Questch, Lauren B. (American Psychological Association, 2022)
"To build healthy and lasting parent-child relationships, parents need practical strategies that meet their child's needs and address the circumstances that affect their families. Written for parents of children from toddlers to teens, this book gives parents a science-based plan to help their children grow up to be emotionally healthy adults. A parent's job unfolds and shifts over time. Concerns about sleep become worries about tantrums; anxieties about sharing become fears about grades and acting out in school. These concerns are natural, but many parents struggle to handle it all. Some feel drained, some lash out, and some feel like the worst parents in the world. This book shows parents how to use a six-step program to build a stronger relationship with their child. It teaches parents how to set parenting goals, prioritize their own emotional health, and create a structure for their family. Having laid that three-step foundation, parents learn the importance of accepting their child for who they are, containing their behavior, and acting as a leader. Prioritizing these six areas and making a plan for them will allow readers to parent proactively rather than reactively and focus on what matters most. No one can be a perfect parent, but you can be a good enough parent, one who shepherds their child toward a healthy, productive adulthood. "--